Indigenous Management Practices: Insights from Latin America (2008)
Management realities in Latin America are rarely examined against the region's changing social, economic, and political backdrop. Managers must reckon with economic volatility, a weak institutional framework, and limited state governance in a diverse organizational landscape where large corporations do not play center stage. Institutional shortcomings, ingrained privilege and exclusion, and rising social demands have bred a flourishing "informal economy "in which more than one-half the labor force earns a living. Together, these circumstances make for a challenging business context where enterprising organizations craft home-grown management practices. This study revisits management practices drawn from in-depth studies of organizations, in Venezuela and Colombia, often deployed by individuals with no formal management training. Hands-on, versatile, and resilient management, strong creative leadership, perseverance and commitment, and keen understanding of the local business context standout as factors that lead individuals to achieve success for their organizations, regardless of the odds.